2019
DOI: 10.1515/ijamh-2019-0083
|View full text |Cite
|
Sign up to set email alerts
|

The association between iron deficiency anemia and febrile seizure

Abstract: Objective Different studies have reported contradictory results regarding the relationship between iron deficiency anemia (IDA) and febrile seizure (FS). The present study was conducted to determine the effect of IDA on FS in children. Patients and methods This case-control study was conducted among 52 children with FS (the case group) and 18 children with afebrile seizures and 51 children with fever without seizures in the age range of 6 months to 5 years admitted to the pediatric ward of Imam Khomeini Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…The mean MCV for the case group was less than that of the control group (p=0.0004) which is according to the results obtained by Shaikh et al [18] and Kamalammal and Balaji [19]. The mean MCH was significantly lower in cases than that in the control group (p=0.002) which is similar to the studies by Kamalammal and Balaji [19] and Karimi et al [20]. In the present study, the mean MCHC in cases was significantly lower than that in controls (p=0.0001) which is similar to the study by Kamalammal and Balaji [19].…”
Section: Discussionsupporting
confidence: 87%
“…The mean MCV for the case group was less than that of the control group (p=0.0004) which is according to the results obtained by Shaikh et al [18] and Kamalammal and Balaji [19]. The mean MCH was significantly lower in cases than that in the control group (p=0.002) which is similar to the studies by Kamalammal and Balaji [19] and Karimi et al [20]. In the present study, the mean MCHC in cases was significantly lower than that in controls (p=0.0001) which is similar to the study by Kamalammal and Balaji [19].…”
Section: Discussionsupporting
confidence: 87%
“…The present study revealed that males were more prone to convulsions than females, which is also proven by 10,11 Iron was an important remedy for this age group. It helps transport oxygen to the brain by synthesizing neurotransmitters in dierent brain areas.…”
Section: Discussionsupporting
confidence: 72%
“…A previous meta-analysis by Karimi et al revealed that anemia due to iron deficiency was a predisposing factor for febrile seizures in children. Overall Odd Ratio (OR) on their study was 1.27 [23].…”
Section: Publication Bias and Quality Assessmentmentioning
confidence: 94%